New species and records of linyphiid spiders from Laos (Araneae, Linyphiidae) - Tanasevitch, Andrei V. (Zootaxa, 2014)
Recent linyphiid collections from Laos as well as some additional specimens from Thailand and West Malaysia are examined. Six species and two genera are described as new to science: Bathyphantes paracymbialis n. sp., Nematogmus asiaticus n. sp., Theoa hamata n. sp.; Asiagone n. gen. is erected for Asiagone signifera n. sp. (type species) and A. perforata n. sp.; Laogone n. gen. is established for Laogone cephala n. sp. The following new synonyms are proposed: Gorbothorax Tanasevitch, 1998 n. syn. = Nasoona Locket, 1982; Paranasoona Heimer, 1984 n. syn. and Millplophrys Platnick, 1998 n. syn. = Atypena Simon, 1894; Gorbothorax ungibbus Tanasevitch, 1998 n. syn. = Oedothorax asocialis Wunderlich, 1974; Hylyphantes birmanicus (Thorell, 1895) n. syn. = H. graminicola (Sundevall, 1830). The following new combinations are proposed: Atypena cirrifrons (Heimer, 1984) n. comb. ex from Paranasoona; A. pallida (Millidge, 1995) and A. crocatoa (Millidge, 1995) both n. comb. ex Millplophrys; Nasoona asocialis (Wunderlich, 1974) n. comb. ex Oedothorax Bertkau, 1883; N. asocialis (Wunderlich, 1974), N. comata (Tanasevitch, 1998), N. conica (Tanasevitch, 1998), N. setifera (Tanasevitch, 1998) and N. wunderlichi (Brignoli, 1983), all n. comb. ex Gorbothorax. Eight linyphiid species are newly recorded from Laos: A. cirrifrons (Heimer, 1984), Bathyphantes floralis Tu & Li, 2006, Hylyphantes graminicola (Sundevall, 1830), Nasoona asocialis, N. crucifera (Thorell, 1895), Nasoonaria sinensis Wunderlich & Song, 1995, Neriene birmanica (Thorell, 1887), and N. oxycera Tu & Li, 2006. The linyphiid spider fauna of Laos currently contains 15 species and is unusually highly specific. All species, except the Palearctic H. graminicola, are probably represented by Southeastern Asian or Oriental autochthons.